Biochar-based nano-composites for the decontamination of wastewater: A review. (July 2016) - Tan, Xiao-fei; Liu, Yun-guo; Gu, Yan-ling; Xu, Yan; Zeng, Guang-ming; Hu, Xin-jiang; Liu, Shao-bo; Wang, Xin; Liu, Si-mian; Li, Jiang
Graphical abstract: Highlights: Recent studies on synthesis of biochar-based nano-composites are reviewed. Biochar-based nano-composites combine the advantages of biochar with nano-materials. Nano-particles improve biochar's physicochemical properties and serve as active sites. Multiple mechanisms are involved in contaminants removal. Knowledge gaps in the future development should be studied. Abstract: Synthesizing biochar-based nano-composites can obtain new composites and combine the advantages of biochar with nano-materials. The resulting composites usually exhibit great improvement in functional groups, pore properties, surface active sites, catalytic degradation ability and easy to separation. These composites have excellent abilities to adsorb a range of contaminants from aqueous solutions. Particularly, catalytic material-coated biochar can exert simultaneous adsorption and catalytic degradation function for organic contaminants removal. Synthesizing biochar-based nano-composites has become an important practice for expanding the environmental applications of biochar and nanotechnology. This paper aims to review and summarize the various synthesis techniques for biochar-based nano-composites and their effects on the decontamination of wastewater. The characteristic and advantages of existing synthesis methods are summarized and discussed. Application of biochar-based nano-composites for different contaminants removal and the underlying mechanisms are reviewed. Furthermore, knowledge gaps that exist in the fabrication and application of biochar-based nano-composites are also identified.